Vivências de professores da rede municipal de Aparecida de Goiânia sobre inclusão escolar - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Researching education in contemporary times demands, above all, respect and commitment to the educational environment, to the experience of the individuals involved; and, in the case of this research, to the experience linked to teaching practice. Understanding the educational universe in its diversities, valuing differences, and understanding that for teaching and learning there are no closed, cast rules, or ready and finished formulas, but rather, the capacity for attentive listening, dialogue, and teacher education that allies theory and practice in search of new learning and new teaching knowledge. For the construction of this research, it was established as a problematizing question: To what extent do teachers of regular classrooms build their teaching knowledge facing inclusive education? Starting from the point that these teaching knowledges are eminently formative and understood both as initial training and continuing education. The overall goal of this research is: to unveil, from the stories told by teachers of a regular school in the municipal system of Aparecida de Goiânia, how the formation process take place for the construction of knowledge regarding inclusive education. And, the specific ones are: to know the experiences of teachers and their experiences with inclusion; to analyze the process of teacher training, both initial and continuing, experienced by teachers in relation to inclusive education; to identify, together with the teachers, based on what they have experienced in their educational career, which factors interfere, facilitate, and/or hinder the implementation of inclusive practices; to promote the reflective action of teachers in inclusive education based on the memory of their own life stories. The methodology used in this process was the qualitative approach with phenomenological approaches. The authors who supported the proposal were: Mazzotta (1998); Mantoan (2003; 2017); Reis (2013), Santos and Reis (2016); Pietro (2006); Teixeira (2002), Freire (1996); Nóvoa (2002; 2007; 2009); Tardif (2012); Tardif, Lessard (2007), among others. The text was organized into four chapters: the first presents the academic and professional trajectory of the researcher emphasizing the reasons for choosing the theme; the second outlines the methodological process of the research and presents the characterization of the school and the participating individuals; the third chapter highlights the main concepts that support this study, as well as the history of inclusive public policies; and, the last chapter presents the data and research analysis from the participants' narratives. The research pointed out the need for greater effort and commitment by the government in the implementation of public policies that favor inclusive education in its various dimensions, especially teacher training. It was also proven that the construction of teachers' knowledge goes through initial education and theoretical knowledge, but it is in practice that this education is consolidated, it is in experience and in the exchange of experience that teachers increasingly acquire a formative baggage to deal with the specificities that arise.
Experiences of teachers of the municipal system of Aparecida de Goiânia about school inclusion
Keywords: Formação docente; Educação Inclusiva; Experiências de professores; Teacher education; Inclusive education; Teachers' experiences; CIENCIAS HUMANAS::EDUCACAO